Analisis Dampak Positif Pelatihan Kewirausahaan Dalam Meningkatkan Omset Penjualan Pelaku Usaha Mikro Kecil Menengah Di Kecamatan Pinang Raya - Puji Odarwani; Metri Hidayati2; Defitriyansyah Defitriyansyah; Sriekowati Sriekowati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
In 2019, the world experienced the COVID-19 pandemic which affected many sectors. The sector most affected by COVID-19 is the economy. One of those affected by the COVID-19 pandemic is MSMEs. MSMEs really felt the decline in sales, lack of capital and hampered distribution. In Pinang Raya sub-district, located in North Bengkulu district, there are many small and medium business actors who experienced a decline in sales during the pandemic era and after the pandemic era, to overcome this, the local government together with the North Bengkulu Cooperative and MSME Service held entrepreneurship training for MSMEs in Pinang Raya sub-district, the training was held at the North Bengkulu KUMKM PLUT in Pinang Raya sub-district. This made the researcher take research on the analysis of the positive impact of entrepreneurship training in increasing the sales turnover of MSMEs in Pinang Raya sub-district. The research method used in this study is a qualitative descriptive method. In this study, the research subjects used were MSMEs in Pinang Raya District who had received Entrepreneurship training. From this study, it was found that the training attended by MSME actors in Pinang Raya Regency had an impact on the continuity of their businesses. There are several things that are affected by the training, 1) income, and 2) sales volume. Both of these things are interrelated. With the Entrepreneurship training, medium-sized MSME actors learn about good and correct leadership. With this leadership, the production output will be better so that it will increase their sales volume. When the sales volume increases, their income will automatically remain. So that their business can be said to have business continuity.